UPAYA MENINGKATKAN KECERDASAN EMOSIONAL SISWA SMB VIHARA VAJRA BODHI MANGGALA MENGGUNAKAN METODE DISCOVERY-INQUIRY LEARNING - Kartika Indah Sundari Kartika Indah Sundari (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2021)
This research aims to describe the increase in emotional intelligence through the discovery inquiry learning method to students Buddhist Vihara Vajra Bodhi Manggala Sunday School Kudus. This is a type of classroom action research, this research consists of 2 cycles with a four-step approach, namely planning, action, observation, and reflection. Data collection techniques using questionnaires, observation, evaluation, and documentation. The results can be proven by the evaluation of students' emotional intelligence 649 or 81.12% in cycle 1 increasing to 684 or 85.5% in cycle 2. 59 or 73.75% in cycle 1 and 76 or 95% in cycle 2. Meanwhile, based on individual observations 552 or 69% in cycle 1 increased to 778 or 97.25 in cycle 2. Based on the results of increasing students' emotional intelligence, it can be concluded that discovery inquiry learning method can improve the emotional intelligence of Vihara Vajra Bodhi Manggala Sunday School students in Kudus.